Adolescents´ perceptions and experiences of empowerment in mental health care : The integrative review - Överlund, Tiina (My University, 2024)
The aim of this bachelor´s thesis was to describe adolescents´ experiences and perceptions of empowerment in mental health care and to identify in what relations these experiences and perceptions of adolescents´ are connected to empowerment. In addition, the aim was to describe the measurements used to measure empowerment. Empowerment has a key role in human rights and building effective services. Adolescence is a significant period in life when adolescents take major leaps forward, developing psychologically, neurologically and physically, and searching for their own identity, taking steps towards becoming an active member of society. Empowering and supporting adolescents in this process is particularly important and crucial task in mental health care. The thesis was conducted as an integrative literature review. The data for the thesis was included through a systematic search of PubMed, CINAHL and psycINFO databases, as well as through a manual search. The database search followed a pre-generated search phrase. A total of 1437 hits were obtained, of which 11 original articles were included according to predefined inclusion and exclusion criteria. The literature search was carried out during spring 2024. The quality of the included original articles was assessed using the Mixed Methods Appraisal Tool and the quality of the included original articles was assessed to be good. Inductive content analysis was used to analyse the data in the review, and the expressions that emerged from the analysis were quantified to identify connections between categories and their strengths. Three upper categories of adolescents’ experiences and perceptions of empowerment were identified: interaction, environment and actual power. The results highlighted a sense of being encountered, involvement and power to oneself and supporting structure. In exploring the connections between the categories, three levels of empowerment were identified in the experiences and perceptions of adolescents that are the individual level, the level of mental health care and the level of social environment. The most used measurement of adolescents´ empowerment in mental health care was The Youth Efficacy/Empowerment Scale—Mental Health. The importance of being encountered was emphasized, particularly in relation between the levels of individual and mental health care. Involvement occurred exclusively in connection between the mental health care level and the individual level. Adolescents emphasized having actual power as empowering and wanted to be as active agents in mental health care. Having a power over one´s life and oneself was experienced at all the levels. Even though, the individual level was highlighted in the experiences and perceptions, adolescents connected supporting structure to empowerment.
Keywords: adolescence, adolescent, empowerment, psychiatric care, mental health care